Commonly encountered symptoms and their management in patients with cirrhosis - Philips, Cyriac Abby (Frontiers in Medicine, 2024)
This exhaustive review, explored the multifaceted symptoms and their management in patients with cirrhosis. Patients frequently endure pain, muscle cramps, sleep disturbances, psychological distress, and gastrointestinal issues, significantly impairing their quality of life.Pain is prevalent, often requiring analgesics, while muscle cramps affect up to 68% of patients, treated with supplements like zinc and taurine despite limited evidence. Sleep disturbances, including insomnia and excessive daytime sleepiness, afflict up to 80% of patients, managed through lactulose, melatonin, and cognitive behavioral therapies. Gastrointestinal symptoms, affecting 80%, include abdominal pain and bloating, necessitating lifestyle and dietary 2 adjustments. Mental health disorders, such as depression and anxiety, are common, managed with a blend of pharmacotherapy and psychotherapy. Sexual dysfunction, often overlooked, profoundly impacts both men and women, requiring holistic treatment approaches. Pruritus, another distressing symptom, is managed with moisturizers and antihistamines, though many treatments show limited success. Hair loss and skin changes add to the psychological burden, highlighting the need for a comprehensive, multidisciplinary approach. The review underscores the imperative for tailored, compassionate care to enhance patient outcomes and quality of life in cirrhosis.